Investing for sustainable climate services: Insights from African experience - Mairi Dupar; Lena Weingärtner; Sarah Opitz-Stapleton (Overseas Development Institute (ODI), 2021)
Effective weather and climate information services ('climate services') are essential to enable people across the world to cope with climate variability and change. Accurate, timely, relevant and usable information can help people to understand their climate-related risks and act appropriately. It can support decision horizons ranging from the daily to the decadal, including plans and activities to adapt to climate change. Effective, sustained delivery of climate services are integral to achieving the Paris Agreement's adaptation goal 'of enhancing adaptive capacity, strengthening resilience and reducing vulnerability to climate change'. The WISER programme aims to strengthen the capacity for climate services delivery in Africa. It is running from 2016 to 2021 and is funded by the UK's Foreign and Commonwealth Development Office (FCDO). This technical report presents the findings of a study on whether WISER projects create sustained capacity for effective climate services delivery. The study also assessed what future climate services programmes and projects can learn about sustainability from the WISER experience. The technical report is accompanied here by a policy brief, which puts forward recommendations for stakeholders based on the findings of the study.
Keywords: 330; sub-Saharan Africa; Climate change; Climate finance